Entrevista motivacional para estudantes de graduação dos diferentes cursos na área da saúde da Pontifícia Universidade Católica do Rio Grande do Sul - Souza , Fernanda Pasquoto de (2015)
This dissertation deals the use of Motivational Interviewing with undergraduate students in the senior year from different healthcare courses. Initially, it is presented a general contextualization of the current research from both a theoretical and a practical point of view. Therefore, three different studies were performed. The first paper aimed to, through an unsystematic review of literature, know the MI trainings offered to health professionals. The second used a crosssectional design in a sample of 120 undergraduate students in the senior year from Medicine, Physiotherapy, Dentistry, Psychology, Nursing, and Nutrition School in order to evaluate the knowledge level of the Motivational Interviewing basic skills. The Confidence and Importance level of using these basic skills in participants' daily practice was also verified. The third using a pre and post-test quasi-experimental design, sought to examine the effectiveness of the eight hour Motivational Interviewing basic skills training with 60 undergraduate students in the senior year from different healthcare courses. Taken together, our results have important implications for the dissemination of the relevant to offer Motivational Interviewing training for undergraduate students from different healthcare courses.